Literature Review: Factors Affecting White Rice Glucose Levels - Hidayati, Intan Nur; Sarbini, Dwi; Purwani, Eni; Kurnia, Pramudya (Journal La Lifesci, 2025)
The high level of rice consumption in Indonesia is due to the belief that people have not eaten if they have not consumed white rice. Based on data from the BPS (2023), Indonesian people's rice consumption reached 31.54 million tons. The biggest content of white rice is carbohydrate content. Carbohydrates are broken down into glucose when they enter the body. White rice has higher glucose levels than brown rice, namely 25.40 per 100 grams (Diyah et al., 2018). According to Susanti & Bistara (2018), most diabetes mellitus sufferers experience hyperglycemia because they tend to consume foods with high glucose. Factors that influence white rice glucose levels are storage temperature, storage time, rice variety and cooking method. The aim of this research is to examine articles regarding factors that influence white rice glucose levels. The research method used is a literature review which examines articles from 2013-2023 of Google Scholar, Garuda, PubMed, Science Direct and Semantic Scholar with indexes Sinta 1-5 or Scopus Q1-Q4. Key words used are kadar glukosa, suhu penyimpanan, waktu penyimpanan, metode pemasakan, rice cooker, magicom, kukus, panggang, bakar, varietas beras putih, nasi putih, storage temperature, storage time, cooking method, steamed roasted, roasted grilled, white rice varieties, glucose content and white rice. Articles were selected using the PRISMA method. From the results of the literature review, it shows there is an influence of storage temperature (50%), storage time (25%), rice variety (50%) and cooking method (67%) on white rice glucose levels.